Metode Block Access Serta Memanejemen Bandwith Pada Mikrotik Rb951ui Dan Mikrotik Rb 941-2ND Di Caffe Ready Jombang Jawa Timur - Akbar Prananda Akbar (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
The most important aspect of a network security system is to maintain data integrity and ensure the availability of services that are used by users safely. All types of attacks and attempts to abuse network resources by irresponsible parties must be overcome in an effort to protect the network security system. As in the case that occurred at Cafe Ready Stadion, it shows that network security at Café Ready Jombang Stadium is still relatively low. Such as abusing an unhealthy network, causing the entry of viruses into the ISP's Internet Service Provider, resulting in unstable Internet Service Provider (ISP) lines. However, this can be overcome by utilizing the block access method and bandwidth management. With the Management Banwith it can limit any use of internet services and can be configured on the MikroTik router software, where there are 2 different MikroTik namely MikroTik RB951Ui-2HnD and MikroTik RB941-2nD. So that there will be a significant difference between the two Mikrotik routers. Namely in terms of capacity and processor of each router. Thus, the purpose of this research is to show the difference between a combination of dividing internet access by providing bandwidth to each user in the form of a hotspot and closing an internet access permanently, so that only certain users cannot access the internet network.